Inventarisasi Hama Dan Penyakit Tanaman Jagung (Zea mays L.) dan Pengendaliannya - Ria Megesari; Mohamad Nuryadi (Musamus Journal of Agrotechnology Research, 2019)
Corn is an annual plant and in one life cycle is completed in 80-150 days where the first half of the cycle is the vegetative growth stage and the second half for the generative growth stage. The purpose of this study was to determine the types of pests and diseases in corn and its control. This research was conducted using interviews with farmers and direct observation in the field. The results obtained in the field are made up of three pests and the two most common types of diseases. The types of pests found consisted of cob borer (Helicoverpa armigera Hubner.), Stem borer (Ostrinia furnacalis) and grasshoppers (Oxya sp.), While the diseases found were cob rot and seed rot, and leaf foliage (Rhizoctonia solani Kuhn). keywords: inventory, plant protection, corn